Isolated Gastrocnemius Recession for the Treatment of Achilles Tendinopathy. Issue 1 (February 2018) - Smith, Kenneth S.; Jones, Caleb; Pinter, Zachariah; Shah, Ashish
Background: Various treatment modalities have been described for Achilles tendinopathy with varying degrees of success. The rationale for the gastrocnemius recession procedure is to decrease the mechanical overload of the Achilles tendon arising from an equinus contracture. Methods: We retrospectively reviewed 25 patients who underwent an isolated gastrocnemius recession procedure at our institution between May 2013 and April 2015 by a single surgeon. Clinical outcome was evaluated on the basis of pain, utilizing visual analog scale (VAS) scores and the Foot Function Index (FFI) by telephonic interview. Student's t test and one-way analysis of variance were used for statistical analysis. Results: The average age of patients was 53.2 years with an average body mass index of 35.8 kg/m 2 . The average follow-up was 13.1 months. All 25 patients had a decrease in VAS scores from an average of 8.9 preoperatively to 2.0 at the 6-week visit. The average FFI went from 73.5 preoperatively to 27.4 at final follow-up. Two out of 25 patients had a postoperative sural neuritis with a total complication rate of 12%. Twenty-one of 25 patients (84%) reported total or significant pain relief. Conclusion: The medium-term results of our study suggest that an isolated gastrocnemius recession is a simple, effective, and safe surgical procedure for the treatment of Achilles tendinopathy. Levels of Evidence: Therapeutic, Level IV: Retrospective